Authoritarianism in an age of democratization - Brownlee, Jason, 1974- (Cambridge University Press, 2007)
"Far from sweeping the globe uniformly, the "third wave of democratization" left burgeoning republics and resilient dictatorships in its wake. Applying more than a year of original fieldwork in Egypt, Iran, Malaysia, and the Philippines, Jason Brownlee shows that the mixed record of recent democratization is best deciphered through a historical and institutional approach to authoritarian rule. Exposing the internal organizations that structure elite conflict, Brownlee demonstrates why the critical soft-liners needed for democratic transitions have been dormant in Egypt and Malaysia but outspoken in Iran and the Philippines."--Jacket